CHALLENGES AND PROSPECTS OF MULTIMEDIA STAGING IN THE EDUCATIONAL THEATRE: THE UNIZIK EXAMPLE - OKEKE, Tochukwu J (UI Scholars Hub, 2023)
At the turn of the century, theatre practice embraced digital technology as an aid towards the achievement of multifarious effects in the theatre. The problem of this study therefore is to examine the effectiveness of multimedia staging technique in an Educational theatre in Nigeria using the performance of Esiaba Irobi’s Colour of Rusting Gold at the Nnamdi Azikiwe University Theatre as a case study. Through the participant observation approach of the qualitative research method, the study interrogates the challenges and problems of the new media employed in multimedia staging in a Nigerian Educational Theatre. The study finds that due to the dearth of state-of-the-art digital staging equipment that the desired effects of multimedia staging is lost on the audience. It thus recommends the re-equipment of Educational Theatres for optimum positive effects of multimedia staging and concludes that the Nigerian Educational Theatre has the potentials of meeting global best practices in theatre design and technology if adequate equipment are provided for the training of theatre professionals.